The Development of a Web-Based MyHr Organization System - Shamsuddin, Muhamad Redhuan; Darman, Rozanawati (Applied Information Technology And Computer Science, 2024)
The web-based MyHr Organization System was developed and designed specifically for Opensoft Technologies company manage employee-related information online. The staff of this Opensoft Technologies firm is the system’s targeted users. Administrators from human resources will handle the responsibility of keeping this website. The manager is also responsible for assigning tasks and reviewing leave applications made by staff. Meanwhile, employees are able to apply for leave using this web system. In addition, managers and staff are able to get reports related to salary and leave releases. The development of this system is based on the Waterfall model. The software used is Microsoft Visual Studio Code as an Integrated Development Environment (IDE) and the database used is phpMyAdmin. Overall, the implementation of the MyHr system empowers companies, like Opensoft Technologies, to address the challenges associated with managing employee information efficiently.